A pandemia da COVID-19 e as medidas de enfrentamento pelos governos locais: análise do município de Campo Belo-MG - Neves Filho, Octávio De Almeida (2023)
The work proposes to analyze measures to combat COVID-19 at the local level, considering the various municipal decrees published to address the issue. A study was carried out in the municipality of Campo Belo, Minas Gerais. Considering the relevance of the reflexes and effects of the pandemic on society as a whole and the way in which government measures were implemented and implemented, a survey of the decrees published in the Official Gazette of the municipality of Campo Belo – MG was carried out with the aim of mapping and analyze the main actions adopted by the municipality, considering the fact that there was no federal coordination to combat the pandemic, within a year of the pandemic. In general, the objective of the research is to analyze the measures to combat COVID-19 in the Municipality of Campo Belo – MG and specifically to analyze the federative lack of coordination in combating the pandemic, verifying public policies to combat COVID-19, with the establishment of a relationship between the number of decrees published and the number of cases of the disease. Furthermore, the work uses a typology of classification of decrees proposed by Rocha and collaborators (2020). Analysis of the decrees shows that “health” and “containment, mitigation and suppression” measures are more present at times of high numbers of cases, deaths and hospitalizations. “Economic compensation” measures would be observed in times of decline.